Optimization of momentum of muon beam and thickness of cell-window for muon experiment in bio-sample: a simulation study - Pant, Amba Datt (BIBECHANA, 2022)
In order to study the bio-samples (aqueous solutions) using muon spin rotation and relaxation (mSR) method, the optimization of momentum of incident muon beam and selection of material for window of sample cell towards muon side are the initial steps for the mSR measurement. Rather than several experimental trials, we used to perform simulation study to optimize the momentum of muon beam and thickness of window of the sample cell. Monte Carlo simulation for optimization of momentum of monoenergetic surface muon beam in different material/thickness of window of the sample cell indicates that the Al or Kapton window of thickness less than 0.3 mm is suitable to maximize the intensity of the stopped muons (momentum between 25.8 MeV/c to 29.8 MeV/c) within 1 mm of water (bio-samples). This simulation will help to design the sample cell for the study of application of muon in life science. BIBECHANA 19(2022)160-164